1981
DOI: 10.1073/pnas.78.3.1542
|View full text |Cite
|
Sign up to set email alerts
|

Specific binding of eukaryotic initiation factor 2 to satellite tobacco necrosis virus RNA at a 5′-terminal sequence comprising the ribosome binding site

Abstract: The mRNA-binding property of eukaryotic initiation factor 2 (eIF-2) was examined by studying its interaction with satellite tobacco necrosis virus (STNV) RNA carrying a 32P-labeled 5' end. The RNA molecules bound by limiting amounts of eIF-2 were isolated and digested with pancreatic and TI RNases. Digestion patterns showed that the labeled STNV RNA preparation offered to eIF-2 was heterogeneous, containing more than 30 different 5' ends; by contrast, the RNA selected by eIF-2 possessed predominantly one 5' en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1983
1983
2004
2004

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…Eukaryotic initiation factor eIF4B has been observed to bind to sequences in satellite tobacco necrosis virus RNA containing the AUG initiation codon (2) and was found to bind preferentially to AUG triplets (14). Initiation factor eIF2 can interact with various RNA molecules that contain AUG codons (23,35); however, the exact binding sites for eIF2 on these RNAs have not been reported. More recently, Dasso et al provided evidence that selection of the 5Ј-proximal start site in influenza virus N2 RNA can be influenced by eIF2 levels (8).…”
Section: Discussionmentioning
confidence: 99%
“…Eukaryotic initiation factor eIF4B has been observed to bind to sequences in satellite tobacco necrosis virus RNA containing the AUG initiation codon (2) and was found to bind preferentially to AUG triplets (14). Initiation factor eIF2 can interact with various RNA molecules that contain AUG codons (23,35); however, the exact binding sites for eIF2 on these RNAs have not been reported. More recently, Dasso et al provided evidence that selection of the 5Ј-proximal start site in influenza virus N2 RNA can be influenced by eIF2 levels (8).…”
Section: Discussionmentioning
confidence: 99%
“…First, capping of full-length STNV RNA does not enhance initiation complex formation whereas capping of 5'-terminal fragments has a stimulatory effect (26). Second, the preferential binding of eIF-2 to full-length and nearly full-length STNV (14) suggests that eIF-2 recognizes a conformation present only in larger molecules. A secondary structure model for STNV-1 RNA in which nt 24 to 55 are interacting with nt 979 to 1009 was proposed (14).…”
mentioning
confidence: 99%
“…7). It has also been reported that eIF2 interacts directly with the 5Ј end of STNV RNA, and this may also play a role in the recruitment of a 40 S ribosome to the 5Ј end (69). However, eIF2 did not bind specifically to the 5Ј-UTR of STNV-1 in the nitrocellulose binding assay (data not shown).…”
Section: Stnv-1 Ted Functions As a Cap Mimic In The 3ј-utr-mentioning
confidence: 76%